2011
DOI: 10.1007/s12325-011-0087-0
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Microlife BP A200 Plus and Omron M6 Blood Pressure Monitors to Detect Atrial Fibrillation in Hypertensive Patients

Abstract: These results indicate that OMRON M6 is more accurate than Microlife BP A200 Plus in detecting AF in patients with essential hypertension. Widespread use of these devices in hypertensive patients could be of clinical benefit for the early diagnosis and treatment of this arrhythmia and related consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 14 publications
5
78
1
Order By: Relevance
“…There were 10 studies with a single set of inclusion criteria (cohort or one-gate studies), 19,60,[63][64][65][66][67][68][69] three studies with two sets of inclusion criteria (case-control or two-gate studies) [70][71][72] and two studies of unclear design. 73,74 One of the case-control studies grouped participants into those with known sustained AF, those with other non-AF arrhythmias and those in sinus rhythm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 10 studies with a single set of inclusion criteria (cohort or one-gate studies), 19,60,[63][64][65][66][67][68][69] three studies with two sets of inclusion criteria (case-control or two-gate studies) [70][71][72] and two studies of unclear design. 73,74 One of the case-control studies grouped participants into those with known sustained AF, those with other non-AF arrhythmias and those in sinus rhythm.…”
Section: Methodsmentioning
confidence: 99%
“…Reasons for exclusion were that the study was not a DTA study; that the target condition was not AF (this included studies in which DTA data for AF could not be extracted, for example when AF and atrial flutter were combined); that the information was not per person (i.e. the unit of analysis was not the person, for example the unit of analysis was the reading or the segment of a reading); population reasons (people Four studies awaiting assessment (see Table 1 Seventeen publications 19,36,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] (15 studies) containing 56 comparisons of an index test with the reference standard were found to meet the full set of eligibility criteria and were included in the review. One publication contained two eligible studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, it may lead to either starting or not starting antihypertensive medication depending on the choice of the device of the studied manufacturers. On the other hand, no differences were observed between measured BP using Omron or Microlife devices in a recent study with focus on the detection of atrial fibrillation in hypertensive patients [16]. Kewalbansing et al [17] compared Omron HEM-SOLAR and Microlife BP3AS1-2 in Surinam and found that Microlife device underestimated systolic BP when compared with Omron and sphygmomanometer.…”
Section: Discussionmentioning
confidence: 97%